Empowerment of Mustahik Based on Zakat Community Development in South Sulawesi (International Journal of Environmental Sciences, 2025)
The main problem in this research is the Empowerment of Mustahik Based on Zakat Community Development (ZCD) in South Sulawesi. This main issue is elaborated into several sub-problems: the model of mustahik empowerment based on ZCD in South Sulawesi; monitoring and evaluation by zakat institutions regarding the sustainable implementation of the ZCD program; and the opportunities and challenges of empowering mustahik through the ZCD program in South Sulawesi. This research is qualitative with a phenomenological approach. The data sources are zakat management institutions and mustahik. Data collection methods include observation, interviews, documentation, and reference searches. Data analysis is conducted through four stages: data collection, data reduction, data presentation, and conclusion drawing. The study reveals that the empowerment of mustahik based on ZCD in South Sulawesi includes the utilization of zakat; enhancing mustahik capabilities; instilling mustahik confidence; providing opportunities; cultivating a sense of responsibility; and offering support. Monitoring and Evaluation of the ZCD program include planning, improvement, priority programs, and capacity building. The opportunities and challenges of mustahik empowerment based on ZCD in South Sulawesi consist of strengths such as empowerment covering various aspects of life; weaknesses such as limited assistance; opportunities such as a high level of program success; and challenges like minimal public understanding. The implications of this research include: presenting a new perspective on zakat-based empowerment programs; offering insights into maintaining the ZCD program not only as a top-down initiative but also as a bottom-up process rooted in community needs and local commodities; and exploring the opportunities and challenges of the ZCD program in South Sulawesi.